IMPROVING STUDENTS’ READING COMPREHENSION USING PROJECT-BASED LEARNING - Celine Lumanauw; Nihta Liando; Fivy Andries (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The aim of this research was to find out whether the use of Project-Based Learning is effective in improving the eighth grade students’ ability in reading comprehension or not. The research was conducted at SMP Berea Tondano. The class consists of twenty students as the subject of the study. This research is quantitative research with one group pre-test and post-test design. Pre-test was given before the treatment. After giving the treatment, the writer collected the data for post-test. The test that used in this test was multiple choice. In this research, the maximum score of the students is 9 and minimum score is 3. The result of this research showed that the mean score of pre-test is 5.00 and post-test is 7.25. This means that the result of post-test is higher than pre-test. This result may lead to conclusion that using Project-Based Learning was considered effective to improve students’ ability in reading comprehension.